2006
DOI: 10.1186/1471-2458-6-209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DOTS expansion on tuberculosis related outcomes and costs in Haiti

Abstract: Background: Implementation of the World Health Organization's DOTS strategy (Directly Observed Treatment Short-course therapy) can result in significant reduction in tuberculosis incidence. We estimated potential costs and benefits of DOTS expansion in Haiti from the government, and societal perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…The cost of health services (for public TB centre) was slightly lower in pulmonary TB than in extrapulmonary TB because the extrapulmonary TB patients did not carry out laboratory tests and X-ray examination in the TB centres, as patients went to the centre after having done their diagnostic tests The total direct expenditure to the health services for pulmonary TB treatment in the current study is comparable to the cost reported in a study in India which were US$30 to US$43 according to the category of treatment [8]. On the other hand, very high expenditure was found in the study conducted in Haiti where the total direct expenditure for pulmonary TB was US$ 432 per TB patient [18], while in another study conducted in Malaysia, the total direct expenditure to the health services for pulmonary TB was US$ 189.50 [7].…”
Section: Discussionsupporting
confidence: 73%
“…The cost of health services (for public TB centre) was slightly lower in pulmonary TB than in extrapulmonary TB because the extrapulmonary TB patients did not carry out laboratory tests and X-ray examination in the TB centres, as patients went to the centre after having done their diagnostic tests The total direct expenditure to the health services for pulmonary TB treatment in the current study is comparable to the cost reported in a study in India which were US$30 to US$43 according to the category of treatment [8]. On the other hand, very high expenditure was found in the study conducted in Haiti where the total direct expenditure for pulmonary TB was US$ 432 per TB patient [18], while in another study conducted in Malaysia, the total direct expenditure to the health services for pulmonary TB was US$ 189.50 [7].…”
Section: Discussionsupporting
confidence: 73%
“…To Steffen et al (2010), the ICER was USD 6,616 per completed DOT treatment [13]. Studies conducted in Ecuador and Haiti suggest that implementation of DOT would result in benefits for the government and society after a 20-year period [21,22]. Other studies did not find any benefits justifying implementation of DOT to combat tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was measured as the number of lives saved, corresponding to patients cured as a result of the adopted strategy [21][22][23].…”
Section: Effectivenessmentioning
confidence: 99%
“…[15,16] In the Indian study, the cost of health services was US$46.00, whereas in the Pakistan study, the cost amounted to US$50.26. On the other hand, very high expenditures were determined in the Haitian study, [17] which evaluated the total direct medical cost per PTB patient to be US$432.00. The Malaysian, [3] Ethiopian, [12] Brazilian, [18] and Tanzanian [19] studies reported that the total direct medical cost of treating a PTB patient was US$95.60, US$189.50, US$103.00, and US$115.30, respectively.…”
Section: Discussionmentioning
confidence: 99%